Identification of multiple risk loci and regulatory mechanisms influencing susceptibility to multiple myeloma - Went, Molly; Bertsch, Uta; Bandapalli, Obul Reddy; Brenner, Hermann; Canzian, Federico; Chen, Bowang; Försti, Asta; Goldschmidt, Hartmut; Hemminki, Kari; Hillengaß, Jens; Thomsen, Hauke; Weinhold, Niels (Nature Communications, 2018)
Genome-wide association studies (GWAS) have transformed our understanding of susceptibility to multiple myeloma (MM), but much of the heritability remains unexplained. We report a new GWAS, a meta-analysis with previous GWAS and a replication series, totalling 9974 MM cases and 247,556 controls of European ancestry. Collectively, these data provide evidence for six new MM risk loci, bringing the total number to 23. Integration of information from gene expression, epigenetic profiling and in situ Hi-C data for the 23 risk loci implicate disruption of developmental transcriptional regulators as a basis of MM susceptibility, compatible with altered B-cell differentiation as a key mechanism. Dysregulation of autophagy/apoptosis and cell cycle signalling feature as recurrently perturbed pathways. Our findings provide further insight into the biological basis of MM., Multiple myeloma is a cancer of the plasma cells, and the complete aetiology of the disease is still unclear. Here the authors perform an additional GWAS analysis followed by a meta-analysis with existing GWAS and replication genotyping and identify 6 novel risk loci and utilise gene expression, epigenetic profiling and in situ Hi-C data to further our understanding of MM susceptibility.
Molly Went, Asta Försti, Niels Weinhold, Bowang Chen, Uta Bertsch, Obul R. Bandapalli, Jens Hillengass, Federico Canzian, the PRACTICAL consortium Hauke Thomsen, Hartmut Goldschmidt, Kari Hemminki [und weitere]; The PRACTICAL consortium Hermann Brenner [und weitere]
Gesehen am 16.07.2019